A Case Report of Spontaneous Resolution of Tractional Retinal Detachment in a Diabetic Patient - Shama Sharief; Syed Mohideen Abdul Khadar (TNOA Journal of Ophthalmic Science and Research)
A 50-year-old female with type 2 diabetes and macular tractional retinal detachment in the right eye was planned for panretinal photocoagulation followed by pars-plana vitrectomy. Two weeks post laser -vision improvement was observed, along with the resolution of the tractional retinal detachment (TRD). In conclusion, spontaneous resolution of macular TRD and reattachment of macula post laser is extremely rare. A possible cause is posterior vitreous detachment (PVD), which relieves traction. If this occurs, the patient may be spared the need for a vitrectomy.